Linezolid Dosing in Patients With Liver Cirrhosis: Standard Dosing Risk Toxicity. Issue 6 (December 2019) - Luque, Sonia; Muñoz-Bermudez, Rosana; Echeverría-Esnal, Daniel; Sorli, Luisa; Campillo, Nuria; Martínez-Casanova, Javier; González-Colominas, Elena; Álvarez-Lerma, Francisco; Horcajada, Juan Pablo; Grau, Santiago; Roberts, Jason A.
Abstract : Background: Limited data regarding altered linezolid pharmacokinetics in patients with liver cirrhosis are available. The objective of this study was to evaluate the pharmacokinetics, efficacy and safety of linezolid in cirrhotic patients. Methods: A case–control 1:1 study of patients undergoing linezolid therapeutic drug monitoring was conducted between January 2015 and June 2017. Cases with liver cirrhosis were matched with controls by age, body weight, comorbidities, renal function, and intensive care unit (ICU) admission. Results: Fifty-two patients were included, 26 in each group. Patients with Child–Pugh Scores A, B, and C were 1 (3.8%), 13 (50.0%), and 12 (46.2%), respectively. Cases had higher median linezolid trough plasma concentrations than controls [20.6 (17.4) versus 2.7 (11.3); P < 0.001)] and more frequently achieved an optimal pharmacodynamic index [26 (100%) versus 16 (61.5%); P = 0.002]. In addition, potentially toxic concentrations and treatment discontinuation due to overexposure and hematological toxicity were also more frequently seen in cirrhotic patients. Overall clinical cure rate was high (67.4%), and in-hospital mortality was 28.8%. No differences in clinical outcomes were observed between both groups. Conclusions: Linezolid showed a high clinical cure rate. Nevertheless, plasma concentrations and treatment discontinuation due to hematological toxicity were higher in cirrhotic patients. Liver cirrhosis may influence linezolid pharmacokinetics and question the use of standard doses. Therapeutic drug monitoring of linezolid would be valuable in these patients.